Correlation of Clinical, Arthroscopic, and Immunological Parameters in Patients with Mandibular head fractures - Khasapetov, Б. С. (Actual Dentistry, 2025)
Abstract. One of the possible etiological factors of postoperative complications in patients with condylar head fractures (CHFs) is the traumatization of joint soft tissue elements during fracture and surgical procedure, as well as a cascade of molecular immune reactions that are triggered by trauma, which causes the development and progression of pathological changes in TMJ. Aim: determine the relationships between clinical, arthroscopic, and radiological indicators, as well as the content of pro-inflammatory cytokines in the synovial fluid and TMJ capsule in patients with CHFs in the early and late posttraumatic period, as well as to determine their influence on the functional results after open reduction and osteosynthesis in patients of this category. Results and Conclusions. In the case of CHFs with a displacement of fragments, a complex of internal disorders develops in the TMJ, which consists of the formation of hemarthrosis (52%), the development of acute synovitis with hyperemia and vessel injection of capsula and retrodiscal tissues, as well as disc dislocation with hyperextension and ruptures of the posterior ligament of the articular disc. After 4 months, the manifestations of acute synovitis decrease, but dystrophic changes corresponding to the initial stages of osteoarthritis become more pronounced. These changes occur against the background of an increase in the content of pro-inflammatory cytokines (TNF-α, CCL4), vascular endothelial growth factor (VEGF), and fibroblast growth factor (FGF4). After 4 months, cytokine levels in most patients decreased by an average of 70.5 ± 24.6%, which is a sign of normalization of the functional state of the damaged joint. However, some patients had an increase in cytokine levels, which can be considered a sign of a breakdown of adaptive and compensatory mechanisms and creates prerequisites for the chronicity of inflammatory processes and the development of dystrophic changes with the formation of osteoarthritis. There are statistically significant correlations between clinical, immunological, and arthroscopic parameters, essential for determining the long-term functional prognosis and developing a strategy for preventing complications. Thus, type C fractures are associated with a higher frequency of signs of acute traumatic arthritis (capsular hyperemia, vascular injection) and increased levels of VEGF (r = – 0.72; p < 0.05) and CCL4 (r = – 0.7; p < 0.05) are associated with a decrease in mouth opening in the late postoperative period. In addition, there is a probable relationship between the degree of capsule hyperemia and the presence of crunching in the TMJ, which, according to our study, was observed in 33% of patients (r = 0.48; p < 0.05).